Collaborative Religious Coping as a Mediator Between Attachment to God and Forgiveness - Adib Ahmad; Hanifah Latif Muslimah; Putri Triana Agustina (UIN Sunan Kalijaga, 2025)
This research aims to investigate the mediating role of collaborative religious coping in the relationship between attachment to God and forgiveness. The sample consists of 198 students from one of the faculties at a leading state university (PTN) in Indonesia, located in Yogyakarta. Three scales were administered: the Forgiveness Scale, the Attachment to God Scale, and the Collaborative Religious Coping Scale. The results of the structural equation model regression analysis showed that collaborative religious coping mediating the relationship between attachment to God and forgiveness. Attachment to God has a significant positive effect on collaborative religious coping and forgiveness. However, collaborative religious coping did not have a significant effect on forgiveness, so the mediating effect of collaborative religious coping in the relationship between attachment to God and forgiveness was not significant. These findings imply that a personal and secure attachment to God may serve as an independent spiritual resource that directly fosters forgiveness, suggesting that the role of collaborative religious coping may be more situational than central. The discussion explores the underlying reasons for these outcomes, providing a deeper understanding of the dynamics at play. Penelitian ini bertujuan untuk menyelidiki peran mediasi koping religius kolaboratif dalam hubungan antara kelekatan terhadap Tuhan dan pemaafan. Sampel terdiri dari 198 mahasiswa dari salah satu fakultas di Perguruan Tinggi Negeri (PTN) terkemuka di Indonesia, yang berlokasi di Yogyakarta. Tiga skala yang digunakan: Skala Pemaafan, Skala Kelekatan terhadap Tuhan, dan Skala Koping Religius Kolaboratif. Hasil analisis regresi model persamaan struktural menunjukkan bahwa koping religius kolaboratif memediasi hubungan antara kelekatan terhadap Tuhan dan pemaafan. Kelekatan terhadap Tuhan berpengaruh positif signifikan terhadap koping religius kolaboratif dan pemaafan. Namun, koping religius kolaboratif tidak berpengaruh signifikan terhadap pemaafan, sehingga efek mediasi tidak signifikan. Temuan ini mengindikasikan bahwa kelekatan yang aman kepada Tuhan dapat berfungsi sebagai sumber daya spiritual yang berdiri sendiri dan secara langsung menumbuhkan kemampuan memaafkan, sehingga peran collaborative religious coping lebih bersifat situasional daripada menjadi faktor utama. Diskusi studi ini menggali alasan yang mendasari hasil tersebut untuk memberikan pemahaman yang lebih mendalam mengenai dinamika yang terjadi.